Impacts on a ralo tropical forest with paca in the south amazon jungle of Peru - Vásquez Flores, Marco Antonio (2022)
The impacts made in a sparse tropical forest with bale in the southern Amazon rainforest of Peru by various activities of extraction of natural resources, can be restored with the appropriate measures and procedures that must be initiated before deforestation, during activities and later with revegetation. To minimize the impacts and compensate for deforestation, it is necessary to design a strategy for the restoration of the tropical forest in the intervened area to achieve a recovery of the affected ecosystem and seek to give a direct benefit to the communities by supporting their self-sustainable development. The resulting indicators must be monitored for 3 years, with physical visits and an additional 10 years using remote technology.